Electromagnetic wave absorption properties of Ca1-xCexFe0.5Mn0.5O3–δ ceramics prepared by a sol–gel combustion method. Issue 5 (1st March 2023) - Xiang, Ri; Cheng, Lichun; Qi, Haiying; Wang, Man; Yao, Qingrong; Chen, Yucheng; Hu, Chaohao; Zhou, Huaiying
Abstract: In this study, porous Ce-doped CaFe0.5 Mn0.5 O3–δ (CFMO) with good microwave absorption properties is reported for the first time. Herein, Cex Ca1−x Fe0.5 Mn0.5 O3−δ (x = 0, 0.05, 0.1, 0.15) (Ce-CFMO) sample powders were prepared by sol–gel method after calcination at 750 °C. Ce-CFMO was characterized by XRD, SEM, TEM, XPS, and VSM, and the Ce-CFMO was also mixed with paraffin wax for VNA. The addition of Ce led to enhanced porosity, enhanced interfacial polarization, enhanced defect polarization, and higher oxygen vacancy content in the CFMO. This resulted in enhanced charge polarization and dipole polarization as well as significant optimization of the impedance matching of CFMO. The unique pore structure of the CFMO is the main reason for its microwave absorption performance. Moreover, the preparation method of this material is simple and its cost is low, providing it with wide application prospects. CFMO has not yet been applied in the field of microwave absorbing materials, and there is still a lot of room for development in the future.